Proceso de atención nutricional en paciente masculino de 62 años de edad con diagnóstico de ogilvie y esquizofrenia. - Chela Mullo, Daysi Jhomayra (2023)
The clinical case of a 60-year-old male patient with a diagnosis of Ogilvie and Schizophrenia is presented. Ogilvie Syndrome is a normal intestinal dysfunction through the colon without an obvious mechanical cause, and Schizophrenia is a neuropsychiatric disorder of unknown etiology. The objective of this clinical case is to assess the nutritional status of the patient through anthropometric, biochemical, clinical/physical and dietary indicators, to obtain a nutritional diagnosis and intervene with a dietary plan according to the patient's nutritional needs, allowing favorable results. evidenced in nutritional monitoring.